Implementation of the Independent Curriculum in Christian Education Lessons - Tjandra, Daniel Sudibyo (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
The education curriculum in Indonesia continues to evolve with the times. Recently, the education system transitioned from the 2013 Curriculum to the Merdeka Curriculum. This research aims to analyze the implementation of the Merdeka Curriculum in Christian Education Lessons, highlighting its impact and effectiveness. The significance of this study lies in its contribution to understanding curriculum development in Indonesia and how the Merdeka Curriculum aligns with national educational goals and the Pancasila student profile. A literature review methodology was employed, gathering relevant information from the Google Scholar database and other sources. Data were analyzed using a SWOT framework to identify key considerations in implementing the Independent Curriculum, aiming to maximize opportunities and minimize threats. The findings indicate that the Merdeka Curriculum aligns with the vision of Indonesian Education, promoting life competencies in students. This vision supports the Pancasila student profile, emphasizing differentiated learning to meet individual student interests and needs. The analysis involved a systematic literature review, data extraction, and SWOT analysis to synthesize and interpret the findings.